A Proresolving Peptide Nanotherapy for Site‐Specific Treatment of Inflammatory Bowel Disease by Regulating Proinflammatory Microenvironment and Gut Microbiota. Issue 18 (1st August 2019) - Li, Chenwen; Zhao, Yang; Cheng, Juan; Guo, Jiawei; Zhang, Qixiong; Zhang, Xiangjun; Ren, Jiong; Wang, Fengchao; Huang, Jun; Hu, Houyuan; Wang, Ruibing; Zhang, Jianxiang
Abstract: The incidence and prevalence of inflammatory bowel disease (IBD) increases steadily worldwide. There is an urgent need for effective and safe IBD therapies. Accelerated resolution of inflammation is a new strategy for the management of inflammatory diseases. For effective and safe IBD treatment, herein a smart nanotherapy (i.e. oxidation‐responsive nanoparticles containing a proresolving annexin A1‐mimetic peptide Ac2‐26, defined as AON) is developed, which can release packaged Ac2‐26, in response to highly expressed reactive oxygen species (ROS) at diseased sites. AON effectively protects Ac2‐26 from degradation in the enzyme‐rich environment of the gastrointestinal tract. By delivering this nanotherapy to the inflamed colons of mice with IBD, site‐specific release and accumulation of Ac2‐26 in response to high levels of ROS at the inflammatory sites are achieved. Mechanistically, the Ac2‐26‐containing, oxidation‐labile nanotherapy AON effectively decreases the expression of proinflammatory mediators, attenuates trafficking and infiltration of inflammatory cells, promotes efferocytosis of apoptotic neutrophils, and increases phenotypic switching of macrophages. Therapeutically, AON reduces symptoms of inflammation, accelerates intestinal mucosal wound healing, reshapes the gut microbiota composition, and increases short‐chain fatty acid production. Additionally, oral delivery of this nanomedicine shows excellent safety profile in a mouse model, conferring the confidence for further development of a targeted precision therapy for IBD and other inflammatory diseases. Abstract : A reactive oxygen species‐responsive, proresolving peptide nanotherapy is developed for effective and safe treatment of inflammatory bowel disease, by regulating proinflammatory microenvironment and gut microbiota.